UV photodetection properties of pulsed laser deposited Cu-doped ZnO thin film. Issue 5 (1st April 2017) - Shewale, P.S.; Yu, Y.S.
Abstract: Nanocrystalline undoped and 2 at% copper (Cu) doped zinc oxide (ZnO) thin films were successfully grown onto SiO2 /n-Si substrates at 600 °C by using pulsed laser deposition (PLD) technique. The influence of Cu incorporation on structural, surface morphological, elemental composition and UV detection properties of ZnO film was investigated. X-ray diffraction studies of thin films show that they are polycrystalline and have a hexagonal wurtzite structure; however, Cu doping improves the preferential orientation along c-axis. The chemical state of constituent elements was analysed by X-ray photoelectron spectroscopy (XPS). It indicates the presence of Cu ions in the doped film that exist in a mixed univalent and bivalent state. FE-SEM observations support the crystallographic results. The effective incorporation of Cu ions into the lattice of the ZnO nanostructure without changing its wurtzite structure was confirmed by an energy dispersive X-ray spectroscopic analysis (EDX). The UV photodetection characteristics of both films were further studied in metal-semiconductor-metal (MSM) planar configurations at room temperature and are found to be greatly influenced by Cu doping. The incorporation of Cu into ZnO lattice increases the resistivity of thin film; which leads to lower dark current. As a result, the Cu-doped ZnO film based UV PD demonstrates improved UV sensitivity of about 66.92 upon 2 mW/cm 2 UV illumination at 365 nm peak wavelengths and 5 V applied bias. The reproducible UV detection performance of MSM devices was also ensured by periodically switching UV light on and off at fixed time intervals.